![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
= \(\frac{1}{2}\)- \(\frac{2}{3}\)+ (\(\frac{3}{4}\)- \(\frac{3}{4}\)) + ( -\(\frac{4}{5}\)+ \(\frac{4}{5}\)) + ( \(\frac{5}{6}-\frac{5}{6}\)) - \(\frac{6}{7}\)
= \(\frac{1}{2}-\frac{2}{3}-0-0-0-\frac{6}{7}\)
= \(\frac{1}{2}-\frac{2}{3}-\frac{6}{7}\)
=\(\frac{21}{42}-\frac{28}{42}-\frac{36}{42}\)
= \(\frac{-43}{42}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 = (1 + 9 ) + (2 + 8 ) + (3 + 7) + (4 + 6) + 5
=10 + 10 + 10 +10 +5
= 40 + 5
= 45
kb nhé
1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9
= (1 + 9) + (2 + 8) + (3 + 7) + (4 + 6) + 5
= 10 + 10 + 10 + 10 + 5
= 40 + 5
= 45
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{2^{10}.3^8-2.\left(2.3\right)^9}{2^{10}.3^8+\left(2.3\right)^8.2^2.5}\)
\(A=\frac{2^{10}.3^8-2^{10}.3^9}{2^{10}.3^8+2^{10}.3^8.5}\)
\(A=\frac{2^{10}.3^8\left(1-3\right)}{2^{10}.3^8\left(1+5\right)}\)
\(A=\frac{1-3}{1+5}=\frac{-1}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3-\left(\frac{6}{7}\right)^0+\left(\frac{1}{2}\right)^2:2\)
\(=3+1+\frac{1}{4}:2\)
\(=4+\frac{1}{8}\)
\(=\frac{33}{8}\)
Ai cung sai z - - 1 phải = + 1 chứ
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=3-1+\frac{1}{2^2.2}\)
\(=2+\frac{1}{8}=\frac{17}{8}\)
2+3=5,1+6=7,2+6+7=15
2+3= 5
1+6= 7
2+6+7=15
Chúc bạn học giỏ